2005
DOI: 10.1007/s11167-005-0517-3
|View full text |Cite
|
Sign up to set email alerts
|

Complexation of Lead(II) Ions with Hydroxide Ions in Nitrate-Chloride Solutions

Abstract: Complexation of lead(II) ions with hydroxide ions in nitrate-chloride solutions at 298 K was studied using potentiometric titration.The search for the optimal composition of the alkaline electrolyte is an important technological task in processing of scrap lead accumulators with an active paste containing lead(II) oxide [1].The high solubility of PbO in alkaline solutions is known to be due to formation of strong lead(II) hydroxide complexes [2,3]. The presence of both organic and inorganic admixtures and, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…As has already been stated, at low [OH – ]/[Pb 2+ ] ratios solid oxide clusters are formed due to Pb­(OH) 2 precipitation which are then converted to PbSe clusters by reaction with free selenide anions. Increasing this ratio leads to the formation of Pb­(OH) 3 – complexes. , If cation solution concentration is high enough for saturation, direct precipitation of nanocubic PbSe occurs which are subsequently deposited through OA. During growth, the cation concentrations are continuously depleted and once a critical point is reached where precipitation is no longer favorable, the PbSe particles may redissolve, giving rise to pure IBI mechanism.…”
Section: Results and Discussionmentioning
confidence: 99%
“…As has already been stated, at low [OH – ]/[Pb 2+ ] ratios solid oxide clusters are formed due to Pb­(OH) 2 precipitation which are then converted to PbSe clusters by reaction with free selenide anions. Increasing this ratio leads to the formation of Pb­(OH) 3 – complexes. , If cation solution concentration is high enough for saturation, direct precipitation of nanocubic PbSe occurs which are subsequently deposited through OA. During growth, the cation concentrations are continuously depleted and once a critical point is reached where precipitation is no longer favorable, the PbSe particles may redissolve, giving rise to pure IBI mechanism.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Although it is doubtful if the simple hydroxide Pb(OH)2 is stable in the solid state,4 some research has studied the crystal structure of lead hydroxide [4][5][6]. Previous studies have shown that the Pb(OH) 2 precipitates can form in solution at low sodium hydroxide concentrations [7,8]. However, the morphology of Pb(OH) 2 precipitates has rarely been reported.…”
Section: Introductionmentioning
confidence: 99%
“…[31]. The content of lead hydroxide in precipitates may be attributed to the relative low concentration of alkali (0.03 M), [28,29] compared to 0.2M sodium hydroxide in Ref. [31].…”
mentioning
confidence: 99%
“…[27] Previous studies have shown that Pb(OH) 2 precipitates can form in solutions at low sodium hydroxide concentrations. [28,29] However, the morphology of Pb(OH) 2 precipitates has rarely been reported. The previous morphology of lead hydroxide crystal is plate-like in the work by Sole and Yoffe.…”
mentioning
confidence: 99%